Urgensi Ilmu Mukhtalif Al-Hadits dalam Ijtihad: Telaah atas Hukum Menjama’ dan Mengqadha Shalat - Rubiyanah; Abdul Jalil (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[URGENCY OF THE SCIENCE OF MUKHTALIF AL-HADITH IN IJTIHAD: STUDY THE LAW OF JAMA' AND QADHA PRAYER]. This study examines the hadith which explains about praying without hindrance and reciting it for the dead. This research aims to find out how the law and how to perform 'prayers without hindrance and compare it for the deceased based on the evidence of hadiths, as well as the analysis of fiqh scholars. The method used is tahlili and muqarin, which is to analyze the hadiths that contradict the explicit meaning, then compared between the hadiths with reference to the science of mukhtalif al-hadith. Figures using the tahili method include: Ibn Hajar al-'Atsqalaniy, Al-'Abbas Syihab al-Din Ahmad bin Muhammad al-Qastalani, Syams al-Din Muhammad bin Yusuf bin 'Ali al-Kirmani, Muhammad bin' Abd al-Baqi 'bin Yusuf al-Zarqani. Those who use the method of muqarin are Imam Nawawi and Badr al-Din Abu Muhammad Mahmud bin Ahmad. Differences of opinion among the scholars of fiqh (khilafiyah), because there is no explanation in qath'i both in the Qur'an and Sunnah. From here comes the ijtihad of scholars whose truth is relative (zhanniy). In the matter of the law of praying 'prayers without hindrance, and its qadha for the dead are found hadiths whose explicit meaning contradict each other. The science of mukhtalif al-hadith is a solution in ijtihad to compromise and get legal conclusions. The output of this study makes a positive contribution for Muslims to obtain legal clarity as a practical reference in practice.